Studies on the Chemical Composition of Salai Gum - Bhargava, G. G.; Negi, J. S.; Guha, S. R. D. (Indian Forester, 1978)
The oleo gum resin from Salai (Boswellia serrata) COnsists of 23.5% gum, 55% oil and 55% resin. The gum portion mainly contains D.galactose (46.22%), D-arabinose (11.66%) and 4-D-methyl glucuronic acid alongwith minor quantities of D.mannose and D-xylose in the molecular architect. The gum on methylation and subsequent hydrolysis of methylated product yielded a complex mixture of O-methyl sugars. The main type of linkages in between galactose units were found to be 1â†’3 and 1â†’6.